An Analysis Of Şevket Rado’s Music Articles Published In Akşam Newspaper. - Yıldırım, Tuncay (Electronic Turkish Studies)
Şevket Rado, one of the important actors of the Turkish press in the early Republican period, carried out effective activities in fields such as literature, newspapers, magazines and radio for many years. Rado, who managed to hold a place among the first generation intellectuals of the Republic thanks to her breakthroughs and activities at the institutional level, mostly through her identity as a magazine and newspaper publisher, is not much known about her relationship with the field of music. However, Rado was someone who wrote on various music-related topics, closely followed music institutions and concerts, attended music meetings, and maintained close relationships with and interviewed prominent musicians of his time. At this point, the aim of this research, which has gained scientific meaning and importance because it is the first of its kind, is to identify and analyze Rado's music writing and musical equipment. This research, which examines 37 music articles published in Akşam newspaper between 1940 and 1950 in terms of genre, content and thematic distribution using document analysis and content analysis methods, sheds light not only on Rado's music writing and ideas but also on the musical atmosphere of the period and the current state of music writing. As a result of the research, it is understood that Rado generally used an idealist and unifying language in her writings, published articles on many subjects such as musical institutions, the Turkish-Alaturk dichotomy, radio broadcasting, music education, biography, book reviews, records, gramophones, musical taste, financial matters, and that her ideas were in line with the musical ideal of the period.